Analysis Of Product Quality , Brand Ambassador, And E – WOM On The Decision To Purchase Scarlett Products On Shopee Among The Sidoarjo Community - Ellysa Aristha Dewi; Lilik Indayani (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This research is directed at understanding the effect of Product Quality, Brand Ambassadors, and E-WOM on Purchasing Decisions for Scarlett Products at Shopee among the Sidoarjo Community. This research applies a quantitative approach and the sample used in this research is 100 informants, which are determined through purposive sampling method and data collected using a questionnaire. The population includes people who live in Sidoarjo. Data analysis in this study used the IBM SPSS Statistics Version 27 for windows application. The findings of this study indicate that Product Quality, Brand Ambassador, and E-WOM individually have a significant and positive effect on Purchasing Decisions.